Day/night changes in serum S100B protein concentrations in acute paranoid schizophrenia - Morera-Fumero, Armando L.; Díaz-Mesa, Estefanía; Abreu-Gonzalez, Pedro; Fernandez-Lopez, Lourdes; Cejas-Mendez, Maria del Rosario (Progress in neuro-psychopharmacology & biological psychiatry, 2017)
There are day/night and seasonal changes in biological markers such as melatonin and cortisol. Controversial changes in serum S100B protein levels have been described in schizophrenia. We aim studying whether serum S100B levels present day/night variations in schizophrenia patients and whether S100B levels are related to psychopathology. Sixty-five paranoid schizophrenic inpatients participated in the study. Psychopathology was assessed with the Positive and Negative Syndrome Scale (PANSS) at admission and discharge. Blood was drawn at 12:00 (midday) and 00:00 (midnight) hours at admission and discharge. Sixty-five healthy subjects matched by age, gender and season acted as control group. At admission and discharge patients had significantly higher serum S100B concentrations at midday and midnight than healthy subjects. At admission, patients showed a day/night variation of S100B levels, with higher S100B levels at 12:00 than at 00:00h (143.7±26.3pg/ml vs. 96.9±16.6pg/ml). This day/night difference was not present in the control group. Midday and midnight S100B at admission decreased when compared to S100B at discharge (midday, 143.7±26.3 vs. 83.0±12, midnight 96.9±16.6 vs. 68.6±14.5). There was a positive correlation between the PANSS positive subscale and S100B concentrations at admission. This correlation was not present at discharge. Conclusions: acute paranoid schizophrenia inpatients present a day/night change of S100B serum levels at admission that disappears at discharge. The correlation between serum S100B concentrations and the PANSS positive scores at admission as well as the decrease of S100B at discharge may be interpreted as an acute biological response to the clinical state of the patients. •Controversial changes in serum S100B proteins levels have been described in schizophrenia.•Acute paranoid schizophrenia inpatients have a S100B serum day/night change at admission that disappears at discharge.•The decrease of S100B at discharge may be interpreted as an acute biological response to the clinical state of the patients.